2020
DOI: 10.1002/ese3.736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supercritical, liquid, and gaseous CO2 on fracture behavior in sandstone

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…This reduction is in a good agreement with our results. Similarly, Sun et al (2020), who also explored the effects of CO 2 on mechanical properties, found that when exposed to pressurized CO 2 reservoirs at 6-8 MPa for 30 days, the fracture toughness of sandstone decreases by 11.01%-27.89% compared to that of dry sandstone.…”
Section: Fracture Toughnessmentioning
confidence: 97%
“…This reduction is in a good agreement with our results. Similarly, Sun et al (2020), who also explored the effects of CO 2 on mechanical properties, found that when exposed to pressurized CO 2 reservoirs at 6-8 MPa for 30 days, the fracture toughness of sandstone decreases by 11.01%-27.89% compared to that of dry sandstone.…”
Section: Fracture Toughnessmentioning
confidence: 97%
“…This changes the ability of rocks to resist fracture failure. SEM is used to observe the microscopic structure of rocks in experimental research [32,33]. Therefore, this study applied SEM to observe the granite under different temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers [16][17][18][19][20][21][22][23][24][25] studied the chemical reactions of CO 2 -sandstone-brine under the supercritical condition of CO 2 . Tey found that scCO 2 corroded the mineral surface and disrupted the original pore structure.…”
Section: Chemical Reaction Between Scco 2 and Minerals In Sandstonementioning
confidence: 99%